A Multicenter Randomized Trial of Ibandronate Compared With Single-Dose Radiotherapy for Localized Metastatic Bone Pain in Prostate Cancer - Peter Hoskin; Santhanam Sundar; Krystyna Reczko; Sharon Forsyth; Natasha Mithal; Bruce Sizer; David Bloomfield; Sunil Upadhyay; Paula Wilson; Amy A. Kirkwood; Michael R.L. Stratford; Mark Jitlal; et al. (2015)
The radiotherapy or ibandronate (RIB) trial was a randomized multicenter nonblind two-arm trial to compare intravenous ibandronate given as a single infusion with single-dose radiotherapy for metastatic bone pain. Four hundred seventy prostate cancer patients with metastatic bone pain who were suitable for local radiotherapy were randomly assigned to radiotherapy (single dose, 8 Gy) or intravenous infusion of ibandronate (6mg) in a noninferiority trial. Pain was measured using the Brief Pain Inventory at baseline and four, eight, 12, 26, and 52 weeks. Pain response was assessed using World Health Organization (WHO) criteria and the Effective Analgesic Score (EAS); the maximum allowable difference was ±15%. Patients failing to respond at four weeks were offered retreatment with the alternative treatment. Quality of life (QoL) was assessed at baseline and four and 12 weeks. Because the trial was designed with a 5% one-sided test, we provide 90% confidence intervals (two-sided) for differences in pain response. Overall, pain response was not statistically different at four or 12 weeks (WHO: −3.7%, 90% confidence interval [CI] = −12.4% to 5.0%; and 6.7%, 90% CI = −2.6 to 16.0%, respectively). Corresponding differences using the EAS were −7.5% and −3.5%. However, a more rapid initial response with radiotherapy was observed. There was no overall difference in toxicity, although each treatment had different side effects. QoL was similar at four and 12 weeks. Overall survival was similar between the two groups but was better among patients having retreatment than those who did not. A single infusion of ibandronate had outcomes similar to a single dose of radiotherapy for metastatic prostate bone pain. Ibandronate could be considered when radiotherapy is not available.